Cardiovascular health risk behaviors among college students of Pokhara, Nepal - Shrestha, Kalpana; Shahi, Nikita; Pokharel, Ganga; Shrestha, Chandan (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Cardiovascular diseases (CVDs) are the leading cause of death globally, taking an estimated 17.9 million lives each year. However, most cardiovascular diseases can be prevented by addressing behavioral risk factors. The objective of this study was to identify cardiovascular health risk behaviors among college students of Pokhara. Method: Descriptive, cross sectional, web based study was conducted among 390 college students of Pokhara from 10 June to 30 July, 2021. Online self-administered structured questionnaire was used for data collection using purposive and snowball sampling technique. The collected data were analyzed using descriptive (frequency, percentage, mean, standard deviation) and inferential statistics (Chi square). Result: In this study, smoking, tobacco use and alcohol consumption were present among 33(8.5%), 13(3.3%) and 45(11.5%) respondents respectively. Further consumption of junk food was found among 349(89.5%) followed by screen time of more than two hours among 300(76.9%) respondents. A statistically significant association was found in age (p=0.17) and gender (p<0.001) with smoking. Similarly, statistically significant association was found in gender (p<0.001) with tobacco use and in age (p=0.028), gender (p<0.001), education (p=0.026) and family type (p=0.009) with alcohol consumption. Conclusion: Cardiovascular health risk behaviors such as smoking, tobacco use and alcohol intake was found more among male students. Further consumption of junk food along with screen time of more than two hours was found among most of the college students.